PENGARUH KOMUNIKASI INTERNAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA (Studi Pada Karyawan Outsourching PT. Bank Tabungan Negara cabang Semarang) - Cahyo, Bastian Dwi; Suryoko, Sri; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2014)
Human resources is one of factors has an important role in improving employee performance.Â The population of this study were 86 employees as respondent.Â  From the results of data analysis conclude that Internal Communication has significant effect on Job Satisfaction with 45,8%, Working Environment influence Job Satisfaction with 36,7%, Internal Communication influences Job working performances with 18.5%. Working environment influences workers performances with 10.1%. Job satisfactions influence Workers performance with 11.6%. Together with Internal communication and Working Environment influence workers performance as 19.3%. and together with Internal communication, worker environment and job satisfaction to worker performances as 18.4%. it shows that as the internal communication, worker environment and job satisfaction are going well, the worker performance will going well alsoAccording to this research in the management of Bank Tabungan Negara Company, we have to pay more attention to the internal communication in that company. Good communication, with no obstacle, harmony has always been there so that the workers can work better and move straightly to the goals of the company. The company has to concern about the worker environment so they will feel comfort and happy while doing their works. Job satisfaction has to be concerned, especially among the upper and lower class workers and also with the same class. A harmony and healthy relation has to be kept and the worker environment has to be increased for better future of the company